1989
DOI: 10.1084/jem.169.4.1421
|View full text |Cite
|
Sign up to set email alerts
|

A cytotoxic T lymphocyte inhibits acquired immunodeficiency syndrome virus replication in peripheral blood lymphocytes.

Abstract: CD8+ (suppressor/cytotoxic) lymphocytes block replication of HIV-1 or the simian immunodeficiency virus of macaques (SIVmac) in PBL of infected individuals. We now show that these CD8+ lymphocytes undergo clonal expansion in vivo after AIDS virus infection of the individual, suggesting they may be antigen-specific T cells. These CD8+ cells block replication of virus in autologous but not MHC class I-mismatched PBL. The inhibitory lymphocytes express the integrin family molecule 4B4 and the CTL-associated S6F1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(110 citation statements)
references
References 24 publications
4
106
0
Order By: Relevance
“…The potential role of CD8 + cells in preventing virus production after acute infection of PBMC of asymptomatic individuals is supported by previous findings that these cells have anti-HIV suppressing activity (Brinchmann et al, 1990;Tsubota et al, 1989;Walker et al, 1986Walker et al, , 1991a. Moreover, in an earlier study of superinfection, Kannagi et al (1990) demonstrated in preliminary studies that CD8 + cells from asymptomatic individuals do not lyse CD4 + cells infected with an exogenous virus, thus suggesting a suppressing mechanism.…”
Section: Discussionsupporting
confidence: 66%
“…The potential role of CD8 + cells in preventing virus production after acute infection of PBMC of asymptomatic individuals is supported by previous findings that these cells have anti-HIV suppressing activity (Brinchmann et al, 1990;Tsubota et al, 1989;Walker et al, 1986Walker et al, , 1991a. Moreover, in an earlier study of superinfection, Kannagi et al (1990) demonstrated in preliminary studies that CD8 + cells from asymptomatic individuals do not lyse CD4 + cells infected with an exogenous virus, thus suggesting a suppressing mechanism.…”
Section: Discussionsupporting
confidence: 66%
“…There is controversy regarding the mechanism of CD8+ T cell-mediated inhibition of HIV replication in vitro. It has been argued that CD8^ cells mediate suppression of HIV replication in vitro without killing CD4ĉ ells [28], but others [17] have suggested that this effect is mediated by CD8^ cytotoxicity. Zarling et al [24] reported that CD8^ T cells from HIV-infected individuals, but not chimpanzees, have circulating cytotoxic T lymphocytes that lyse activated autologous HIV-infeeted and -uninfected CD4T cells.…”
Section: Discussionmentioning
confidence: 99%
“…While it is known that this activity is not mediated by CD16^/CD8^ NK cells [17], the mechanism by which CD8+ cells from HIV-infected individuals inhibit viral replication in vitro is subject to controversy. CD8^ T cells are known to exert their effector function by lysing infected cells in an MHCrestricted antigen-specific fashion [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations